The BEN Domain Protein Insensitive Binds to the Fab-7 Chromatin Boundary To Establish Proper Segmental Identity in Drosophila. Issue 2 (8th June 2018) - Fedotova, Anna; Aoki, Tsutomu; Rossier, Mikaël; Mishra, Rakesh Kumar; Clendinen, Chaevia; Kyrchanova, Olga; Wolle, Daniel; Bonchuk, Artem; Maeda, Robert K; Mutero, Annick; Cleard, Fabienne; Mogila, Vladic; et al.
Abstract: Boundaries (insulators) in the Drosophila bithorax complex (BX-C) delimit autonomous regulatory domains that orchestrate the parasegment (PS)-specific expression of the BX-C homeotic genes. The Fab-7 boundary separates the iab-6 and iab-7 regulatory domains, which control Abd-B expression in PS11 and PS12, respectively. This boundary is composed of multiple functionally redundant elements and has two key functions: it blocks cross talk between iab-6 and iab-7 and facilitates boundary bypass. Here, we show that two BEN domain protein complexes, Insensitive and Elba, bind to multiple sequences located in the Fab-7 nuclease hypersensitive regions. Two of these sequences are recognized by both Insv and Elba and correspond to a CCAATTGG palindrome. Elba also binds to a related CCAATAAG sequence, while Insv does not. However, the third Insv recognition sequences is ∼100 bp in length and contains the CCAATAAG sequence at one end. Both Insv and Elba are assembled into large complexes (∼420 and ∼265–290 kDa, respectively) in nuclear extracts. Using a sensitized genetic background, we show that the Insv protein is required for Fab-7 boundary function and that PS11 identity is not properly established in insv mutants. This is the first demonstration that a BEN domain protein is important for the functioning of an endogenous fly boundary.